Regulation of the Zinc Deficiency Response in the Legume Model Medicago truncatula - Liao, Feixue; Lilay, Grmay Hailu; Castro, Pedro Humberto; Azevedo, Herlander; Assunção, Ana G. L. (Frontiers in Plant Science, 2022)
The Zn deficiency response in Arabidopsis is regulated by F-bZIP transcription factors, and there is evidence of evolutionary conservation of this regulatory network in land plants. Fundamental knowledge on the Zn homeostasis regulation in crop species will contribute to improving their Zn nutritional value. Legumes are protein-rich crops, used worldwide as part of traditional diets and as animal forage, being therefore a good target for micronutrient biofortification. Here, we identified F-bZIP transcription factors in representative legume species and functionally characterized the two F-bZIPs from M. truncatula. Results indicate that MtFbZIP1 is the functional homolog of Arabidopsis bZIP19 and bZIP23, while MtFbZIP2 does not play a role in the Zn deficiency response. Additionally, analysis of M. truncatula genes from the ZIP family of Zn transporters and NAS enzymes that produce the Zn ligand nicotianamine (NA), support the conservation of the F-bZIP-regulated Zn deficiency response in M. truncatula. Phylogenetic analysis of F-bZIP homologs enriched in legume species reinforces the branching into two groups, with MtFbZIP1 and MtFbZIP2 mapping in Groups 1 and 2, respectively. This phylogeny combined with the functional characterization of MtFbZIPs supports the suggested conservation of the Zn deficiency response associated with Group 1 F-bZIPs, and the more variable evolutionary paths associated with Group 2. Overall, we provide novel insight on the mechanisms of response to Zn deficiency in M. truncatula. The characterization of the MtFbZIPs regulatory network will help developing strategies for improving Zn content in legume crops.